Keefektifan Konseling Kognitif dengan Strategi Reframing untuk Meningkatkan Konsep Diri Akademik Siswa SMA - Ujang Abdul Basir; M. Ramli; Adi Atmoko (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: The purpose of this research is improving academic self-concept in high school students by a cognitive group counseling activities with reframing techniques modivication. The type of research used quasi experimental design that is non-equivalent control group design. The results of this study showed that there is an increase in students academic self-concepts. This is evidenced by the acquisition of Mann-Withney U between the experimental group and the control group with a value Asymp. Sig. (2-tailed) of 0,27 and this results less than 0,5 so it can be concluded that cognitive group counselling with reframing techniques is effective for improving academic self-concept in high school students. The conclusion of this research is the students academic self-concepts in islamic high school Al-Maarif Singosari improved after given cognitive group counselling services with reframing techniques.   Abstrak: Tujuan penelitian ini yaitu untuk meningkatkan konsep diri akademik siswa SMA melalui kegiatan konseling kelompok kognitif yang dimodifikasi dengan teknik reframing. Penelitian ini merupakan quasi experimental design dengan jenis non-equivalent control group design. Hasil dari penelitian ini menunjukkan adanya peningkatan konsep diri akademik yang dimiliki siswa SMA. Hal ini dibuktikan dengan perolehan hasil uji Mann-Whitney U antara kelompok eksperimen dan kelompok kontrol yaitu dengan nilai Asymp. Sig. (2-tailed) sebesar 0,27 dan hasil ini kurang dari 0,5 sehingga dapat ditegaskan bahwasanya konseling kelompok kognitif dengan strategi reframing efektif untuk mengubah konsep diri akademik siswa SMA. Kesimpulan penelitian ini yaitu konsep diri akademik siswa SMA Al-Maarif Singosari meningkat setelah diberi layanan konseling kelompok kognitif dengan teknik reframing.